Peran Ditsamapta dalam Meningkatkan Pelayanan Publik untuk Mewujudkan Polisi Republik Indonesia yang Presisi - Aprianty, Henny; Rudiyanto, George; Dani, Rahiman; Purnawan, Heru; Yanto, Hernowo Novi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2023)
The Directorate of Samapta (Ditsamapta) is a work unit at the Polda level under the Kapolda. Samapta is in charge of carrying out four activities namely Arrangement, Guard, Escort and Patrol (Turjawali). Crowd control (Dalmas). Seacrh And Rescue (SAR), as well as Animal Assistance (k-9). Samapta's main task is to carry out the function of the police as a preventive or preventive task against violations of the law or disruption of the Kamtibmas, carry out early stages of repressive action as well as other forms of disturbance of the Kamtibmas. Efforts to carry out police functions according to Law of the Republic of Indonesia Number 2 of 2002 concerning the Police of the Republic of Indonesia